Physical Exercise Training Effect and Mediation Through Cardiorespiratory Fitness on Dual-Task Performances Differ in Younger–Old and Older–Old Adults. (23rd May 2019) - Bherer, Louis; Langeard, Antoine; Kaushal, Navin; Vrinceanu, Tudor; Desjardins-Crépeau, Laurence; Langlois, Francis; Kramer, Arthur F
Abstract: Objective: It has often been reported that dual-task (DT) performance declines with age. Physical exercise can help improve cognition, but these improvements could depend on cognitive functions and age groups. Moreover, the mechanisms supporting this enhancement are not fully elucidated. This study investigated the impacts of physical exercise on single- and dual-task performance in younger-old (<70) and older-old (70+) adults. The study also assessed whether the training effect on cognition was mediated by improvement in cardiorespiratory fitness. Methods: One hundred forty-three participants (65–89 years) took part in a physical exercise intervention for 3 months or were assigned to a control group. All participants completed a DT paradigm and an estimated measure of cardiorespiratory fitness. Regression models were used to test the training effect on these outcomes, and mediation analyses were used to determine whether the training-related cognitive changes were mediated by changes in cardiorespiratory fitness. Results: In 70+, training predicted improved processing speed (βc = −.33) and cardiorespiratory fitness (βa = .26) and the effect of training on processing speed was fully mediated by change in cardiorespiratory fitness (βab = −.12). In <70, training predicted improvement in task-set cost (βc = −.26) and change in cardiorespiratory fitness (βa = .30) but improvement in task-set cost was not entirely mediated by change in cardiorespiratory fitness. Discussion: Results are discussed in terms of the mechanisms supporting DT performance improvement following physical exercise training in older adults.